1993
DOI: 10.2134/agronj1993.00021962008500030007x
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield, Quality, Compatibility, and Persistence of Warm‐Season Grass—Legume Mixtures

Abstract: Development of compatible, persistent, wann-season f:rass-legume mixtuns could increase forage yield and quality during summer months. We established a trial to detennine forage yield, quality, species compatibility, and persistence of binary mixtures of wann·st·ason grasses with selected legumes, five of which are native to the ~:entral USA. Grass entries were switchgrass (Panicum virgaJum L.), sideoats grama (Bouleloua curtipendula Michx.), and indiangrass [Sorghastrum nutans (L.) Nash]. Legume entries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
73
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 0 publications
9
73
1
Order By: Relevance
“…Legumes may improve N availability in degraded rangeland ecosystems, while providing a sustainable and higher quality forage resource. Posler et al (1993) Total vegetation yield (planted species yield + resident vegetation yield) responses to the treatments varied by site. At Mason City, the interaction of herbicide and planting treatments was significant (P < 0.05) (Table 5).…”
Section: Lsd (005) -----12 -----8 --16 --------------------------8mentioning
confidence: 99%
“…Legumes may improve N availability in degraded rangeland ecosystems, while providing a sustainable and higher quality forage resource. Posler et al (1993) Total vegetation yield (planted species yield + resident vegetation yield) responses to the treatments varied by site. At Mason City, the interaction of herbicide and planting treatments was significant (P < 0.05) (Table 5).…”
Section: Lsd (005) -----12 -----8 --16 --------------------------8mentioning
confidence: 99%
“…Legumes may improve N availability in degraded rangeland ecosystems, while providing a sustainable and higher quality forage resource. Posler et al (1993) found that certain legumes native to the central Great Plains, e.g., Illinois bundleflower, roundhead lespedeza (Lespedeza capitata Michx. ), and catclaw sensitivebriar [Mimosa quadrivalvis var.…”
Section: ) ----------------------------------------------------------mentioning
confidence: 99%
“…Feed quality of unimproved warm-season pastures in the Southern Great Plains (SGP) can be improved by in-clusion of legumes in the system [1] [2]. Annual forage legumes may be productive during the summer months [3] [4], but their adoption by low-input farmers is often constrained by limited resources for cultivation and sowing.…”
Section: Introductionmentioning
confidence: 99%